1994
DOI: 10.1128/jb.176.15.4700-4709.1994
|View full text |Cite
|
Sign up to set email alerts
|

Two genes for carbohydrate catabolism are divergently transcribed from a region of DNA containing the hexC locus in Pseudomonas aeruginosa PAO1

Abstract: The hexC locus ofPseudomonas aeruginosa PAO1 was localized to a 247-bp segment of chromosomal DNA on the multicopy broad-host-range vector pRO1614. The presence of this plasmid (pPZ196) in strain PAO1 produced the so-called "hexC effect," a two-to ninefold increase in the activities of four carbohydrate catabolism enzymes, glucokinase, glucose-6-phosphate dehydrogenase, 6-phosphogluconate dehydratase, and 2-keto-3-deoxy-6-phosphogluconate aldolase. The extent of the hexC effect was restricted, since three inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 61 publications
1
19
0
Order By: Relevance
“…In P. aeruginosa PAO1, a locus designated hexC (129 bp, cis-element) exists between the gap and edd genes (Temple et al, 1994). This region reportedly contains binding sites not only for HexR but also for the integration-host factor (IHF; Proctor et al, 1997).…”
Section: Hexr May Directly Detect Oxidative Stressmentioning
confidence: 99%
See 2 more Smart Citations
“…In P. aeruginosa PAO1, a locus designated hexC (129 bp, cis-element) exists between the gap and edd genes (Temple et al, 1994). This region reportedly contains binding sites not only for HexR but also for the integration-host factor (IHF; Proctor et al, 1997).…”
Section: Hexr May Directly Detect Oxidative Stressmentioning
confidence: 99%
“…( Fig. 1; del Castillo et al, 2007b;Temple et al, 1994). The first of these pathways is the glucose kinase pathway, in which glucose is transported into the cytoplasm by the glucose transport system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All bacterial species use pathways to reduce NAD + to NADH, for example respiration, which involves either glycolysis and the tricarboxylic acid cycle or fermentation (Jurtshuk, 1996). Bacteria also use NAD + in several forms of dehydrogenases when breaking down aldehydes and alcohols (Kotrbova-Kozak et al, 2007;Luong et al, 2015;Nobelmann & Lengeler, 1996;Temple et al, 1994). NAD is utilized in a number of cellular processes in both bacterial and mammalian cells, for example DNA ligation and repair, redox recycling in the pyruvate dehydrogenase pathway, and synthesis of acetyl-CoA for the tricarboxylic acid cycle (Chalkiadaki & Guarente, 2012;Chiarugi et al, 2012;Ishino et al, 1986;Patel et al, 2014;Satoh & Lindahl, 1992;Wilkinson et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…CCR of toluene metabolism by glucose is mediated by 2-keto-3-deoxy-6-phosphogluconate (KDPG), an intermediate in the Entner-Doudoroff (ED) pathway of glucose metabolism in P. putida Velázquez et al, 2004). Interestingly, the regulation of glucose metabolism is controlled by the HexR repressor (Hager et al, 2000;Petruschka et al, 2002;Temple et al, 1994). We have shown that HexR binding to its cognate operator sites is inhibited by KDPG (Kim et al, 2008).…”
Section: Introductionmentioning
confidence: 99%